Analisis Komparatif SBSN dengan SUN dalam Menangani Defisit APBN - Eba Ismi Alifah (Lisyabab : Jurnal Studi Islam dan Sosial, 2020)
This study is aimed at examining and comparing the effectiveness of state instruments such as SBSN and SUN in financing the APBN deficit. The method used in this writing is a qualitative method (library researchlibrary research). The observation results show that the two instruments have the main function of covering the APBN deficit, but both have very different characteristics. As in the issuance planning stage, sukuk requires an underlying asset while bonds do not. However, bonds have a risk to interest rates while sukuk do not have it because every sukuk issuance must be free from the elements of usury, gharar, and maysir. However, both are equally effective in assisting the government in dealing with the APBN deficit. Both instruments are able to absorb funds from the public that have not been touched by other financial institutions. Although the growth rate of sukuk is still slower than bonds. The existence of sukuk can make an alternative investment instrument for the public that is interest free.